1999
DOI: 10.2176/nmc.39.169
|View full text |Cite
|
Sign up to set email alerts
|

Paroxysmal Kinesigenic Choreoathetosis Associated with Frontotemporal Arachnoid Cyst —Case Report—

Abstract: A 17-year-old male presented with paroxysmal kinesigenic choreoathetosis (PKC) associated with frontotemporal arachnoid cyst. Xenon-133 single photon emission computed tomography detected a slight but equivocal decrease in regional cerebral blood flow in the vicinity of basal ganglia associ ated with the PKC episodes. PKC continued after surgical removal of the cyst but was well controlled by oral administration of carbamazepine.Whether the pathogenesis of symptomatic PKC was associ ated with the cortical lesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…described a case of paroxysmal kinesigenic choreoathetosis associated with a frontotemporal arachnoid cyst. [ 12 ] The authors of that report suggested that the arachnoid cyst might affect the ipsilateral cortico-subcortical connections. Any disturbance in the cortical control of the striatum and its thalamic connection could induce paroxysmal kinesigenic choreoathetosis.…”
Section: Discussionmentioning
confidence: 99%
“…described a case of paroxysmal kinesigenic choreoathetosis associated with a frontotemporal arachnoid cyst. [ 12 ] The authors of that report suggested that the arachnoid cyst might affect the ipsilateral cortico-subcortical connections. Any disturbance in the cortical control of the striatum and its thalamic connection could induce paroxysmal kinesigenic choreoathetosis.…”
Section: Discussionmentioning
confidence: 99%